1996
DOI: 10.1093/infdis/174.6.1348
|View full text |Cite
|
Sign up to set email alerts
|

Lipoteichoic Acid from Viridans Streptococci Induces the Production of Tumor Necrosis Factor and Nitric Oxide by Murine Macrophages

Abstract: Bacterial endotoxin or lipopolysaccharide is the major proinflammatory component of gram-negative bacteria, but the components of gram-positive bacteria that trigger the inflammatory cascade are poorly understood. Lipoteichoic acid (LTA) purified from 2 strains of viridans streptococci induced the accumulation of tumor necrosis factor (TNF) mRNA and protein by the murine macrophage cell line RAW 264.7 in a dose- and time-dependent manner. Furthermore, in the presence of recombinant interferon-gamma, LTA from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 12 publications
1
22
1
2
Order By: Relevance
“…Nevertheless, all of these studies support the notion that contaminating endotoxin in commercially available LTA preparations can and does contribute significantly to the observed biological activity of LTA, even though the role of pure LTA alone in inflammatory cell activation cannot be overlooked. Also worthy of note is a recent report by English et al (8). In those studies, commercially available LTA from gram-positive bacteria S. sanguis and Streptococcus mutans were shown to induce TNF-␣ and NO production from RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, all of these studies support the notion that contaminating endotoxin in commercially available LTA preparations can and does contribute significantly to the observed biological activity of LTA, even though the role of pure LTA alone in inflammatory cell activation cannot be overlooked. Also worthy of note is a recent report by English et al (8). In those studies, commercially available LTA from gram-positive bacteria S. sanguis and Streptococcus mutans were shown to induce TNF-␣ and NO production from RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 90%
“…The host inflammatory response to bacteria is triggered by bacterial products including Gram-negative bacterial endotoxin or LPS, Gram-positive bacterial lipopeptides, bacterial exotoxins, hemolysins, and bacterial DNA (11)(12)(13)(14)(15)(16). Some of these bacterial products are secreted (e.g.…”
mentioning
confidence: 99%
“…Macrophage activation by C 2 -and C 6 -ceramide was not due to contaminating endotoxin Polymyxin B binds to LPS and potently blocks LPS-mediated macrophage activation and inflammatory mediator production [12,16,17]. We found that concentrations of polymyxin B sufficient to block LPS-mediated TNF and iNOS production by RAW 264.7 macrophages had no effect on the ability of either ceramide analog to trigger TNF secretion (Fig.…”
Section: Murine Macrophagesmentioning
confidence: 66%
“…As with many other stimuli [16,21], co-stimulation with low concentrations of rIFN-␥ is necessary for ceramide-induced stimulation of iNOS protein accumulation by these cells. It is interesting that a recent study found that ceramide analogs alone failed to induce iNOS accumulation or NO production in rat primary astrocytes, but that these ceramide analogs greatly augmented the ability of LPS to up-regulate iNOS and NO in these cells [7].…”
Section: Discussionmentioning
confidence: 97%